Electrochemical Determination of Uric Acid Using a Multiwalled Carbon Nanotube Platinum–Nickel Alloy Glassy Carbon Electrode. (2nd January 2017) - Wu, Wenqin; Min, Hui; Wu, Huimin; Ding, Yu; Yang, Shuijin
ABSTRACT: Platinum–nickel nanoparticles were synthesized by a reduction procedure. The Pt–Ni/C composite was characterized by X-ray diffraction, infrared spectroscopy, transmission electron microscopy, and electrochemical analysis. The measurements show that the Pt–Ni/multiwalled carbon nanotubes provided higher electrocatalytic activity for the oxidation of uric acid than Pt–Ni/carbon black. The sensor prepared from the characterized material provided a long linear dynamic range from 0.1 to 240.4 µM with a detection limit of 0.03 µM and a sensitivity of 41.21 µA mM −1  cm −2 . The reported modified electrode also provided excellent selectivity, good stability, and satisfactory reproducibility for the determination of uric acid.